Kritik Metode Kontekstualisasi Penafsiran al-Qur'ān Abdullah Saeed - Imron Mustofa (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article examines the growing movement of thought today, which later becomes known as modernist Islamic thought, especially the idea Abdullah Saeed. For him, a critical attitude towards the source and content of knowledge is necessary internal criticism of Islamic society. This study tries to present data relating to the role of reason behind the idea. Critical reading towards logical framework and epistemology is needed to contextualize dogma, tradition, and culture in order to be transformed to the present. This research gives birth to the perspective that the modernization of Islamic thought is a systematic movement regarding Islamic issues in the ever-changing context. Its characteristics is colored by emphasis on rationality free from sectarianism or exclusivism without claiming finality of thinking. Making interconnectivity (historical context) is the main barometer of interpretation process. The article reveals that Saeed's strategies include four main phases; encounter with the world of the text, critical analysis; meaning for the first recipients and ending with text relating to the up-to-date context. However, excessive exaltation of contextuality will lead to the emergence of an indigenization of the Qur'ān, and even Islam in general.